2022
DOI: 10.1038/s41419-022-04867-w
|View full text |Cite
|
Sign up to set email alerts
|

TDP43 promotes stemness of breast cancer stem cells through CD44 variant splicing isoforms

Abstract: Alternative splicing (AS) is a promising clinical target for cancer treatment at the post-transcriptional level. We previously identified a unique AS profile in triple-negative breast cancer (TNBC), which is regulated by the splicing regulator TAR DNA-binding protein-43 (TDP43), thus indicating the crucial role of TDP43 in heterogeneous TNBC. Cluster of differentiation 44 (CD44), a widely recognized marker for breast cancer stem cells (BCSCs), is extensively spliced into CD44 variant AS isoforms (CD44v) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…In breast cancer, TDP-43 modulates the majority of splicing events via the serine/arginine-rich splicing factor 3 (SRSF3), thereby regulating the progression of triple-negative breast cancer (Ke et al 2018 ). Another study demonstrated that TDP-43 might enhance the stemness of breast cancer stem cells through alternative splicing of the CD44 variant (CD44v) (Guo et al 2022 ). TDP-43 has been identified in melanoma as a novel oncogene that may regulate tumor growth and metastasis by modulating glucose metabolism (Zeng et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, TDP-43 modulates the majority of splicing events via the serine/arginine-rich splicing factor 3 (SRSF3), thereby regulating the progression of triple-negative breast cancer (Ke et al 2018 ). Another study demonstrated that TDP-43 might enhance the stemness of breast cancer stem cells through alternative splicing of the CD44 variant (CD44v) (Guo et al 2022 ). TDP-43 has been identified in melanoma as a novel oncogene that may regulate tumor growth and metastasis by modulating glucose metabolism (Zeng et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive investigations have explored the involvement of TDP-43 in neurodegenerative disorders (de Boer et al 2020 ; Suk and Rousseaux 2020 ; Carlos and Josephs 2022 ). In recent years, TDP-43 has emerged as a vital factor in the advancement of malignant tumors, including breast cancer (Ke et al 2018 ; Guo et al 2022 ), lung cancer (Yang et al 2020 ; Guo et al 2015 ; Chen et al 2018 ), melanoma (Zeng et al 2017 ), liver cancer (Liu et al 2022 ), and ovarian cancer (He et al 2023 ). Studies have demonstrated that TDP-43 interacts with Fas ligand mRNA in lung cancer, enhancing the stability of the Fas ligand mRNA, promoting apoptosis, and ultimately impeding lung cancer growth (Yang et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mainly focused on neurodegenerative diseases, such as Alzheimer’s disease, Parkinson’s disease, and Huntington’s disease [ 55 ]. However, studies have also demonstrated a relationship between TDP43 and a variety of malignancies, such as triple-negative breast cancer [ 56 , 57 ], lung cancer [ 58 ], and melanoma [ 59 ]. In HCC, several studies have reported that TDP43 is upregulated in HCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…While the identities of the RBPs that contribute to this switch in splicing during AML progression are yet to be determined, other RBPs have since been implicated in CSC biology. For example, both SRSF3 and TRA2β are frequently upregulated in breast cancer and regulate the splicing of CD44 leading to the expression of the CD44v isoform that is associated with increased stemness and metastatic traits [ 203 , 204 , 205 ]. Likewise, SRSF1 promotes EMT and cell motility in breast and pancreatic cancer [ 206 , 207 ] and, in APC-deficient colorectal cancer murine models, SRSF1 expression correlates with CSC marker expression maintaining a stemness phenotype by promoting cellular plasticity [ 17 ].…”
Section: Dna Damage Repair In Cscs and Therapeutic Interventionmentioning
confidence: 99%